Alley farming training manual: Core course in alley farming - Reynolds, L.; Atta-Krah, A.N. (International Development Research Centre, 1989)
Presents and discusses the integration of livestock in alley farming and related research activities of ILCA with particular reference to southern Nigeria. Considers the competing demands of crops and livestock for three foliage from alley farms. Discusses the inclusion of a grazed fallow in the system, and describes a more intensive system of tree production to provide animal feed.